A case of enteropathic arthritis complicated by superimposed bilateral septic arthritis of the hips. (3rd April 2021) - Colquhoun, Matthew; Roy, Arpita; Kirresh, Othman; Mouyis, Maria
Abstract: Polyarticular septic arthritis is an underappreciated clinical entity. Pre-existing joint diseases, such as osteoarthritis and rheumatoid arthritis have been shown to be risk factors for septic arthritis. However, there is a paucity of data in the literature regarding the risk of septic arthritis in those patients with enteropathic arthritis. Here, we describe the case of a 47-year-old female with a background history of ulcerative colitis who presented with difficulty mobilising and pain in the hips associated with lethargy, fever and a significant inflammatory response. After an investigative process, she was newly diagnosed with enteropathic arthritis, complicated at presentation, by bilateral septic arthritis of the hips, based on progressive radiological destruction and a joint aspirate that grew Staphylococcus aureus . After treatment with antibiotics and steroids, her pain and mobility significantly improved, and she was discharged with a plan for an elective hip replacement and to commence disease-modifying therapy with sulfasalazine. This case reminds us that we must have a high index of suspicion to diagnose septic arthritis in those who present feverish and unwell with joint pain, even in those who present with multiple joint involvement. Furthermore, it describes a rare occurrence of bilateral septic arthritis of the hips occurring in a patient with enteropathic arthritis, which unlike osteoarthritis and rheumatoid arthritis, is not well described in the literature as a risk factor for septic arthritis.